Analisis pendapatan UMKM di Kawasan Wisata Candi Muaro Jambi (sebelum dan semasa pandemi Covid-19) - Sartika Rakasiwi, Ajeng; Zulfanetti, Zulfanetti; Umiyati, Etik (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
The main objectives of this study are: First, to determine the socio-economic characteristics of MSME actors in the Muaro Jambi temple. Second, analyze the income of MSME actors in Muaro Jambi Temple. Third, knowing the factors that influence the income of MSMEs in Muaro Jambi Temple. Fourth, analyze the impact of Covid-19 on MSME income in the Muaro Jambi temple area. The data used is sourced from the respondent's identity (sample) and a list of questions (questionnaire) conducted in the Muaro Jambi temple area. The sample used in this study was 50 respondents. The method used to analyze this research is descriptive quantitative. This study uses multiple linear regression analysis based on Ordinary Least Square (OLS). The factors that significantly influence this study are labor and length of business. Furthermore, the variables of age and gender have no significant effect. Keywords: Labor, Length of business. Age, Gender, Income